Silicon isotope systematics of acidic weathering of fresh basalts, Kilauea Volcano, Hawai'i. (15th November 2015) - Chemtob, Steven M.; Rossman, George R.; Young, Edward D.; Ziegler, Karen; Moynier, Fréderic; Eiler, John M.; Hurowitz, Joel A.
Abstract: Silicon stable isotopes are fractionated by a host of low-temperature aqueous processes, making them potentially useful as a weathering proxy. Here we characterize the silicon isotope signature of surficial chemical weathering of glassy basaltic lava flows at Kilauea Volcano, Hawaii. Fresh basalt flow surfaces (<40 years old) frequently feature opaque amorphous silica surface coatings up to 80 μm thick. These silica coatings and associated silica cements are enriched in the heavier isotopes of Si (δ 30 SiNBS-28  = +0.92‰ to +1.36‰) relative to their basaltic substrate (δ 30 SiNBS-28  = −0.3‰ to −0.2‰). Secondary clays and opals are typically depleted in 30 Si relative to the dissolved reservoirs from which they precipitated, so this sense of isotopic fractionation is unusual. Mechanisms capable of producing isotopically heavy secondary minerals were explored by conducting batch alteration experiments on fresh basaltic glass. Batch acidic alteration of basalt glass in HCl, H2 SO4, and HF produced silica-rich surface layers resembling the Hawaiian surface coatings. Differences in fluid chemical composition affected the direction and magnitude of Si isotope fractionation. Basalt leaching in HCl or H2 SO4 produced 30 Si-enriched fluids (1000 ln  α precip-Si(aq)  ≅ −0.8‰) and 30 Si-depleted secondary silica layers. In contrast, HF-bearing experiments produced highly 30 Si-depleted fluid compositions (1000 ln  α precip-Si(aq) up to +8‰). Larger isotopic fractionations were observed in experiments with lower fluid–rock ratios. In Hawaii, where altering fluids contain H2 SO4 and HCl but minimal HF, high δ 30 Si values for the silica coatings were likely achieved by Rayleigh fractionation. Aqueous 30 Si-enriched silica was released during incongruent basalt dissolution then subsequently transported and deposited from an evaporating solution at the flow surface. Our results indicate that (1) altering fluid chemistry and fluid–rock ratio impact the Si isotope signature of chemical weathering and (2) δ 30 Si of solids produced by low temperature aqueous alteration may diverge sharply from watershed- or landscape-scale weathering trends.